On the Use of PBIB Designs in Timber Engineering Experiments - Chaubey, A. K.; Sheel, S. K.; Unnikrishnan, K. P. (Indian Forester, 1987)
The use of Partially Balanced Incomplete Block Designs (PBIBD) in timber engineering experiments has been described. The experiments are aimed at estimating the average safe load taken by timber ’joints and comparison of different types of connect dry used in making joints. It has been shown that when the experimental material is not’ available in sufficient quantities or its cost is too prohibitive, PBIB designs are more appropriate than Randomised block designs.